Upaya Meningkatkan Kesadaran Higiene Personal Masyarakat dan Menjamin Kesejahteraan Hewan Ternak dalam Menghadapi Pandemi Covid-19 - Elok Budi Retnani; Rudy Rudy; Desi Nupremani Dermawan; Nadira Fadilah; Felicia Rizal Putri; Virgilius Martin Kelake Kedang; Berlin Berliana Anugrah; Hilman Rizki Pangestu; Januarius Jimi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Thematic community service program which are located in Neglasari and Purwasari villages, Dramaga sub-district, Bogor district has been going well. Several program activities are carried out including the prevention and handling of Covid-19 which aims to prepare the people of Neglasari and Purwasati villages to face the Covid -19 pandemic. The next program is improving the welfare of farmer groups and livestock health, namely a demonstration of how to make probiotics for livestock through a video and poster which is socialized through the WhatsApp communication group. Another program is “ibu cerdas anak sehat” which aims to educate mothers about zoonotic diseases that are often ignored, such as toxoplasma and ringworm and is implemented by distributing leaflets to mothers who attend posyandu. Keywords: COVID-19, Neglasari, Purwasari, Probiotic, Zoonoses